A study of O/X wave data assimilation and inversion for ionospheric vertical electron density profiles - Niu, Longlong; Zhou, Chen; Wei, Na; Deng, Zhong-Xin; Ning, Yun; Chen, Rong; Liu, Wen (Frontiers in Astronomy and Space Sciences, 2025)
Vertical sounding of the ionosphere yields ionograms that reflects the relationship between virtual height and frequency, and electron density profiles can be obtained by inversion of the ionogram. The existing vertical sounding ionogram inversion is mainly based on the model method, but this method has poor stability. Influenced by the geomagnetic field, the electric wave splits into O-wave and X-wave when it propagates in the ionosphere, and this study considers introducing X-wave into the ionogram inversion, and adopts the data assimilation method to improve the stability of the inversion by adding more physical sounding information. Specifically, we take the X-wave trace of the ionogram as the observation value, and the electron density profile obtained from the inversion of the O-wave trace of the ionogram as the background value. Then, the kalman filtering method is used to continuously fuse the observation information into the background information, and correct the background electron density profile. Finally, we select some typical ionograms to verify and analyze the assimilation algorithm, and compared the results with the inversion results of Reinisch algorithm. The results show that the calculated virtual heights of the profiles obtained by the joint inversion of the O-wave and X- wave coincide better with the measured virtual heights, and the fitting error between the synthetic traces of the inverted profiles and the measured traces can be obviously reduced, which indicates that the profiles obtained by the joint inversion of the O-wave and X- wave are closer to the real electron density profile.